REFERENCE EVAPOTRANSPIRATION THROUGHOUT THE STATE OF MINAS GERAIS AS A GUIDE FOR REGIONALIZED IRRIGATION MANAGEMENT - Cunha, Angélica Carvalho [UNESP]; Silva, César De Oliveira Ferreira [UNESP]; Manzione, Rodrigo Lilla [UNESP]; Putti, Fernando Ferrari [UNESP] (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2021)
Minas Gerais is the third Brazilian state with the largest irrigated area, so irrigation management is of paramount importance to ensure the sustainable use of water resources. One way of calculating the water quantity needed for irrigation is by estimating reference evapotranspiration (ETo). Evapotranspiration values are influenced by several climatological factors, such as solar radiation, temperature, vapor pressure deficiency; therefore, evapotranspiration values tend to differ according to each region. Thus, this study proposes the use of a medium reference evapotranspiration map of Minas Gerais as a basis for water management in agriculture. The data were provided by the National Institute of Meteorology (INMET), using Automatic Meteorological Stations (EMAs) located in 49 cities in the state of Minas Gerais. Through the analysis conducted, it was observed that, in mesoregions characterized by greater drought, such as the north of the state, evapotranspiration rates were higher than in more humid mesoregions, which present higher levels of precipitation, such as the Central, Southern, and Mineiro Triangle Regions. Due to its humid characteristic, the region of the Atlantic Forest biome had lower ETo values compared to the Cerrado and Caatinga biomes.
EVAPOTRANSPIRAÇÃO DE REFERÊNCIA AO LONGO DO ESTADO DE MINAS GERAIS COMO GUIA PARA A GESTÃO REGIONALIZADA DA IRRIGAÇÃO
Keywords: Data modeling; Irrigation management; Water management